Applications of telecounselling in spinal cord injury rehabilitation: a systematic review with effect sizes. (December 2013) - Dorstyn, Diana; Mathias, Jane; Denson, Linley
Objective: To investigate the short- and medium-term efficacy of counselling services provided remotely by telephone, video or internet, in managing mental health outcomes following spinal cord injury. Data sources: A search of electronic databases, critical reviews and published meta-analyses was conducted. Review methods: Seven independent studies ( N = 272 participants) met the inclusion criteria. The majority of these studies utilized telephone-based counselling, with limited research examining psychological interventions delivered by videoconferencing ( N study = 1) or online ( N study = 1). Results: There is some evidence that telecounselling can significantly improve an individual's management of common comorbidities following spinal cord injury, including pain and sleep difficulties ( d = 0.45). Medium-term treatment effects were difficult to evaluate, with very few studies providing these data, although participants have reported gains in quality of life 12 months after treatment ( d = 0.88). The main clinical advantages are time efficiency and consumer satisfaction. Conclusion: The results highlight the need for further evidence, particularly randomized controlled trials, to establish the benefits and clinical viability of telecounselling.